Grammar to Vlog : Meaningful and authentic language practice for 21st century ESL learners - Sya'baningrum Prihhartini (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2020)
This study investigated the effectiveness of using Youtube to practice grammar. As Youtube vlogging has become the most current internet phenomena and one of the most sought career choices by today’s young generation, it is one of the most suitable platforms, both to learn and to practice the target language. In this study, 10 first-year university students from an intact-required class participated. The learners were given a task to make a video of them cooking, where they put the targeted grammatical items into use, and then upload it onto Youtube. Videos taken from the learners’ Youtube channels were collected, and qualitative method was utilized to see what strategies the learners employed to bridge the gap between the intended meaning and the lack of grammatical or word knowledge. The findings showed that the learners employed substitution, nonverbal language, and switching to L1 form pattern to overcome the language barrier they encountered during the communicative task. The result of this study shows that Youtube can be used as a meaningful and effective platform to practice grammatical structure, as the learners utilize their skills and strategies for an authentic language use.